The last interview with Don Carlos Aranibar - Chuhue Huamán, Richard (2018)
This essay shares the interview with San Marcos historian Carlos Araníbar Zerpa in 2016. The interview took place in a spontaneous environment, an academic gathering. In this meeting, the teacher cited important data such as the difference between the book by Guamán Poma and that of the Inca Garcilaso de la Vega, considering the first as the most important in the history of Peru. Throughout the interview, notable individuals were mentioned whose intellectual contribution had marked the hearts and minds of many. In the end, it left us with a great message about history and that history must be nourished by other sciences or disciplines in order to enrich oneself with knowledge to have a broader view of the facts.